PENGARUH MODEL PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA SEKOLAH DASAR: PROJECT BASED LEARNING (PJBL) - Humairoh, Siti; Hesti Widiastuti; Jalu Ginanjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing skills are an essential core competence for primary school pupils; however, in practice, many pupils still struggle to express their ideas in a coherent and systematic manner. This study aims to analyse the effect of implementing the Project-Based Learning (PjBL) model on improving the writing skills of Year 5 primary school pupils. The study employed a quantitative approach using a quasi-experimental design of the pre-test–post-test control group type. The research subjects were 50 Year 5 pupils at SDN Lenggahjaya 02, Cabangbungin Sub-district, Bekasi Regency, divided into an experimental class (25 pupils) and a control class (25 pupils). The instrument used was a writing skills test covering five aspects: content/ideas, text organisation, vocabulary use, grammar, and spelling and punctuation. Data analysis was conducted using descriptive statistics, an independent samples t-test, and Normalised Gain (N-Gain) calculations. The results showed that the average post-test score for the experimental class was 82.36, significantly higher than that of the control class at 66.44. The N-Gain score for the experimental class reached 0.63 (moderate category), whilst the control class scored only 0.30 (low category). The t-test yielded a significance level (Sig.) of 0.000 < 0.05, indicating a significant effect. These findings suggest that the PjBL model effectively enhances primary school pupils’ writing skills through a real-world project-based approach that is.